2020
DOI: 10.3389/fneur.2020.547126
|View full text |Cite
|
Sign up to set email alerts
|

Blunted Cardiac Parasympathetic Activation in Student Athletes With a Remote History of Concussion: A Pilot Study

Abstract: Introduction: Blunted cardiac autonomic nervous system (ANS) responses, quantified using heart rate variability (HRV), have been reported after sport-related concussion (SRC). Research suggests this persists beyond clinical recovery. This study compared cardiac parasympathetic responses in student athletes with a remote history of SRC (> 1-year ago, Concussion History: CH) with those who reported no lifetime history of SRC (Concussion Naïve: CN). Design: Retrospective nested case-control. Setting: University l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…Of the included studies, twenty-one were crosssectional studies (Abaji et al, 2016;Bishop et al, 2017;Ding et al, 2020;Dobney et al, 2018;Hanna-Pladdy et al 2001;Hilz et al, 2011Hilz et al, , 2015Hilz et al, , 2016Hilz et al, , 2017Hilz et al, , 2020Howard et al, 2018;Huang et al, 2019;Johnson et al, 2018Johnson et al, , 2020Kozlowski et al, 2013;Mirow et al, 2016;Pyndiura et al, 2020;Russell et al, 2020;Solbakk et al, 2005;Tan et al, 2009;Truong & Ciuffredia, 2016), sixteen were cohort studies (Brandt et al, 2020;Clausen et al, 2016;Dobson et al, 2017;Gall et al, 2004;La Fountaine et al, 2009Leddy et al, 2010;Liao et al, 2016;Purkayastha, Williams et al, 2019;Senthinathan et al, 2017;Wright et al 2017Wright et al , 2018, while two (Haider et al, 2020;Hutchison et al, 2017) were case-control studies. All studies, with the exception of two (Leddy et al, 2010;Mirow et al, 2016), compared mTBI participants to nonhead injured control groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the included studies, twenty-one were crosssectional studies (Abaji et al, 2016;Bishop et al, 2017;Ding et al, 2020;Dobney et al, 2018;Hanna-Pladdy et al 2001;Hilz et al, 2011Hilz et al, , 2015Hilz et al, , 2016Hilz et al, , 2017Hilz et al, , 2020Howard et al, 2018;Huang et al, 2019;Johnson et al, 2018Johnson et al, , 2020Kozlowski et al, 2013;Mirow et al, 2016;Pyndiura et al, 2020;Russell et al, 2020;Solbakk et al, 2005;Tan et al, 2009;Truong & Ciuffredia, 2016), sixteen were cohort studies (Brandt et al, 2020;Clausen et al, 2016;Dobson et al, 2017;Gall et al, 2004;La Fountaine et al, 2009Leddy et al, 2010;Liao et al, 2016;Purkayastha, Williams et al, 2019;Senthinathan et al, 2017;Wright et al 2017Wright et al , 2018, while two (Haider et al, 2020;Hutchison et al, 2017) were case-control studies. All studies, with the exception of two (Leddy et al, 2010;Mirow et al, 2016), compared mTBI participants to nonhead injured control groups.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 4,311 studies were identified, of which, 1,064 duplicates were removed. Two references were shared by a study author (Haider et al, 2020;Pyndiura et al, 2020). The title and abstract of 3,247 studies were screened with 3,092 not meeting inclusion criteria (see Table 2).…”
Section: Study Selectionmentioning
confidence: 99%
“…Concussion-induced brainstem changes might contribute to altered autonomic control of the cardiovascular system in the concussed athletes. We (67,68) and others (4,(69)(70)(71)(72) have found that autonomic control of the heart during a physioloigcal stressor is altered following concussion and might persist wellbeyond symptom resolution (73). Thus, the association among structural brain abnormalities and autonomic function following a concussion warrant further investigation.…”
Section: Lower Body Positive Pressurementioning
confidence: 72%
“…This approach would have allowed us to determine if CA returned to physiological function that is exhibited by healthy controls prior to their return to play. Important emerging evidence indicates that physiological dysfunction persists in concussed patients beyond symptom resolution (4,8,73).…”
Section: Experimental Considerationsmentioning
confidence: 99%
“…The Vagal Tank theory assumes a relative degree of vagal withdrawal (e.g., decrease in HRV) is needed to support metabolically demanding tasks, such as physical exertion [ 42 ]. Preliminary evidence suggests that individuals may demonstrate blunted cardio-autonomic reactivity following concussion [ 65 , 66 ]. Importantly, we observed that fhNDD+ adolescents show minimal to no change in HRV in response to IHGC compared to fhNDD− adolescents during the subacute phase of recovery (<30 days of injury).…”
Section: Discussionmentioning
confidence: 99%